الأصول المتداولة ومدى تأثيرها في التحليل المالي - سعيد حملاوي; محمد الكامل الطاهري; مراد بن السبتي; عبد الحكيم تومي (جامعة الوادي University Of Eloued, 2024)
"الملخص : تمحور الهدف من هذه الدراسة في توضيح مدى تأثير تحليل البيانات المتعلقة بالأصول الجارية في الحصول على مخرجات لتحليل مالي أكثر مصداقية و لتعطي قراءة و واقعية لحاضر و مستقبل المؤسسة ، و كانت تحت الإشكالية الرئيسية التالية : ما مدى تأثير الأصول الجارية على نتائج التحليل المالي للمؤسسة ؟ حيت تطرق الجانب النضري إلى ثلاث مباحث تناول المبحث الأول عموميات عن التحليل المالي والمبحث الثاني مفاهيم عامة حول الأصول الجارية معتمدين فيه على المنهج الوصفي ، ومن أجل الوصول إلى أهداف الدراسة تناولنا في الفصل التطبيقي المنهج التجريبي للتحليل المالي للقوائم المالية لمؤسسة مطاحن قنعوبة و إخوانه ، لمعرفة نتائج تحليل قوائم الأصول الجارية ، وكانت أهم النتائج المتواصل اليها أن تحليل إستخدامات الأصول الجارية للمؤسسة قيد الدراسة أبرزت الواقع المالي الجيد للمؤسسة و الاستقلال المالي الذي يحمي المؤسسة من مخاطر الخسائر والإفلاس. " "Study summary: Our goal in this study is to clarify the extent of the impact of analyzing data related to current assets in obtaining more reliable financial analysis outputs and to give a realistic reading of the present and future of the establishment، and it was under the following main problem: What is the extent of the influence of current assets on the results of the financial analysis of the institution? The theoretical side dealt with three sections. The first section dealt with generalities of financial analysis، and the second section dealt with general concepts about current assets، relying on the descriptive approach. In order to reach the objectives of the study، we dealt in the applied chapter with a study according to the analytical approach of the Ahlam Qanouba and Brothers Mills Foundation، in order to Knowing the results of the analysis of the current assets lists and their impact on the results of the institution’s financial analysis. The most important ongoing results were that the analysis of the uses of the institution’s current assets، Ahlam Mills، highlighted the good financial reality of the institution and the financial independence that protects the institution from the risks of losses and bankruptcy. "
مذكرة ماستر
Keywords: : الأصول الجارية ، التحليل المالي، الإستقلال المالي; القوائم المالية .; current assets، financial analysis، dream mills